PERSEPSI REMAJA TERHADAP KONTEN MEDIA SOSIAL TIKTOK DI JORONG BATU BADINDING UTARA KECAMATAN BONJOL KABUPATEN PASAMAN - Silvia Oktalina; Tomi Hendra (Lembaga Pengembangan Kinerja Dosen, 2023)
Tiktok social media is an application for making short videos supported by music which is very popular with many people. It contains a wide variety of video content. The content that is often seen between one teenager and another is not the same. This brings different perceptions in the lives of adolescents, both with positive and negative perceptions. This study aims to find out how teenagers perceive social media content on Tiktok in North Jorong Batu Badinding. This study uses qualitative methods with a total of 13 key informants. Meanwhile, for data analysis, researchers used three activity lines, namely data reduction, data presentation, and conclusion drawing. The results of this study found positive perceptions of adolescents in Jorong Batu Badinding Utara towards content on social media tiktok, namely the view that content on tiktok is interesting, unique and not boring because the presentation of the duration in the video content is 15 or even 30 seconds, tiktok content contains viral videos educational, informative and entertaining. Tiktok content also contains short tausiyahs that are useful for everyday life. On the other hand, the negative perception of teenagers is that in social media content, TikTok contains lipsync dance video content, content of women dancing while showing their genitals. Content on the TikTok social media contains setting content such as videos of prank shows